Unitary IPSPs enhance hilar mossy cell gain in the rat hippocampus - Kerr, A; Capogna, M (2007)
Mechanisms that control neuronal gain allow for adaptive rescaling to synaptic inputs of varying strengths or frequencies. Here, we show that unitary IPSPs (uIPSPs) modulate gain and unitary EPSP (uEPSP)-action potential coupling in mossy cells (MCs) from rat hippocampal slices. Mossy fibre-evoked uEPSCs were large, facilitated and were suppressed by the group II metabotropic glutamate agonist LY354740. Conversely, uIPSCs were smaller, depressed and were not affected by LY354740, but exerted strong inhibitory control over uEPSP-action potential coupling. The IPSC reversal potential was determined by gramicidin perforated patch recordings to be -65.3 ± 5.0 mV, lying between the resting membrane potential (-75.3 ± 1.1 mV) and the action potential threshold (-56.5 ± 2.4 mV). When applied at theta frequency (10 Hz), uIPSPs increased the offset of the MC input-output response to depolarizing current injection, but also increased gain, maximal firing rate and the slope of the depolarization preceding action potentials. These effects were unchanged by the Ca2+ and HCN channel blockers mibefradil and ZD7288, respectively. The height and maximal slope of MC action potentials during tonic depolarization were also increased by uIPSPs, and the decay of uIPSP conductances injected by dynamic clamp at subthreshold membrane potentials was prolonged by TTX. Application of the muscarinic agonist pilocarpine mimicked the effect of IPSPs on MC maximal firing rate, and action potential height and slope, and this was reversed by the GABAA antagonist gabazine. Thus, uIPSPs can increase neuronal gain under hyperexcitable conditions, and this effect is probably due to the de-inactivation of a TTX-sensitive voltage-dependent Na+ conductance. © 2007 The Authors. Journal compilation © 2007 The Physiological Society.